2011
DOI: 10.1002/jobm.201000321
|View full text |Cite
|
Sign up to set email alerts
|

The paf gene product modulates asexual development in Penicillium chrysogenum

Abstract: Penicillium chrysogenum secretes a low molecular weight, cationic and cysteine-rich protein (PAF). It has growth inhibitory activity against the model organism Aspergillus nidulans and numerous zoo- and phytopathogenic fungi but shows only minimal conditional antifungal activity against the producing organism itself.In this study we provide evidence for an additional function of PAF which is distinct from the antifungal activity against putative ecologically concurrent microorganisms. Our data indicate that PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 57 publications
2
47
0
1
Order By: Relevance
“…The production of PAF[Pc], PAF F31N , PAF Y48Q and NFAP[Pc] required the use of the P. chrysogenum ∆ paf mutant as cell factory, where the paf coding sequence was deleted by replacement with the nourseothricin ( nat1 ) resistance gene [29]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of PAF[Pc], PAF F31N , PAF Y48Q and NFAP[Pc] required the use of the P. chrysogenum ∆ paf mutant as cell factory, where the paf coding sequence was deleted by replacement with the nourseothricin ( nat1 ) resistance gene [29]. …”
Section: Resultsmentioning
confidence: 99%
“…S3). In all P. chrysogenum transformants the nat1 resistant gene was still present that originated from the deletion of the paf gene in the P. chrysogenum Δ paf strain [29] (Additional file 1: Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsitsigiannis and Keller (24) proposed that oxylipins could bind to and sensitize self G protein-coupled receptors, activating downstream signaling cascades. Furthermore, oxylipins regulate conidiation of A. nidulans and Penicillium chrysogenum through the transcription factor Bristle A (BrlA) (28), leading us to suggest that, as in plants and animals, oxylipins might play an important role in the response to injury of T. atroviride through the formation of lipoperoxides along the injured sites and oxylipins could serve as signaling molecules (Fig. S4).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, transcriptome analysis of a T. atroviride ΔnoxR mutant, which fails to develop conidiophores in response to injury, showed that all genes related to oxylipin biosynthesis were either repressed or not responsive to injury, suggesting that oxylipin biosynthesis is compromised in a ΔnoxR mutant background. In this regard, as mentioned above, oxylipins are known to regulate the conidiation of A. nidulans and Penicillium chrysogenum (433,434) and might serve as signaling molecules in the response of T. atroviride to injury.…”
Section: Injury Induces Developmentmentioning
confidence: 97%